Draft Annual Plan 1986-87 Maharashtra State Part One - Planning Commission (Planning Commission, 1986)
The Planning Commission has requested the State Government to formulate the Introduction draft plan proposals for the Annual Plan 1986-87 which will be discussed in the Working Groups meeting of Planning Commission on 30th December, 1985. The Planning Commission in their guidelines for preparation of the draft Annual Guidelines Plan proposals for 1986-87 have indicated that the guiding principles of the Seventh Five Year of the Plan should be taken into consideration while preparing the draft proposals. The Planning Commission has also desired that it should be ensured that adequate provisions are made for Agricultural Development Programmes, Minimum Needs Programme, 20-Point Programme, Tribal Sub Plan, Special Component plan for the welfare of Scheduled Castes and Nava Buddhas and important sectors of Energy and Irrigation. It has also been emphasized in the guidelines that stress should be-on completion of on-going works and capacity utilisation.
Planning Department, Government of Maharashtra